2020
DOI: 10.21608/aimj.2020.28247.1201
|View full text |Cite
|
Sign up to set email alerts
|

Serum Hepcidin In Patients With Chronic Hepatitis C And Its Relation To Treatment With Antiviral Drugs

Abstract: Background: There is a relationship between HCV infection and accumulation of body iron in the liver. Iron overload has been found to be cofactor for HCV associated fibrosis and hepatocellular carcinoma. Hepcidin produced by hepatocytes, is very important in regulation of iron metabolism. Disturbances in Hepcidin concentrations have been reported in chronic HCV infection and hepatocellular carcinoma. The aim of the work: is to measure levels of serum hepcidin in chronic hepatitis C patients and evaluate any as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Hepcidin deficiency causes hereditary hemochromatosis, characterized by body iron overload that may progress into liver cirrhosis (6). In addition, low hepcidin-25 concentration can be induced in iron-loading anemias and chronic hepatitis C (7,8). In contrast, hepcidin synthesis is induced by inflammation and infection (9).…”
Section: Introductionmentioning
confidence: 99%
“…Hepcidin deficiency causes hereditary hemochromatosis, characterized by body iron overload that may progress into liver cirrhosis (6). In addition, low hepcidin-25 concentration can be induced in iron-loading anemias and chronic hepatitis C (7,8). In contrast, hepcidin synthesis is induced by inflammation and infection (9).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that serum markers of iron (e.g. transferrin, ferritin and iron) and liver iron accumulation have positive relation with CHC [8][9] . However, the diagnosis of cirrhosis of the liver with CHC is important as liver fibrosis is most commonly seen in stages III and IV.…”
Section: Introductionmentioning
confidence: 99%